Prispevek k historično-materialističnemu pojmovanju družbenega položaja žensk v kapitalizmu - Rutar, Tibor (Družboslovne razprave, 2013)
The paper aims to explain two claims. First, that gender inequality is not an a historical phenomenon which manifests itself more or less homogenously in all societies or, at least, in class societies, but that it is conditioned by the specific form of social relations of production that characterise such societies. Second, that the question of gender inequality, which is in itself irreducible, remains fundamentally interrelated with the question of class. With regard to theory, we draw upon Marx's critique of political economy while, for the purpose of empirically demonstrating our hypothesis, we turn to historical sources and an analysis of official statistical data.
Keywords: Marksistični feminizem; Marxist feminism; Gender inequality; Spolna neenakost; Kapitalizem; Capitalism; Neoliberalism; Neoliberalizem; woman; ženske; družbeni položaj